Affective symptoms and regional cerebral tau burden in early‐stage Alzheimer's disease. (15th March 2021) - Tommasi, Nicole S; Gonzalez, Christopher; Briggs, Danielle; Properzi, Michael J; Gatchel, Jennifer R; Marshall, Gad A; ,
Abstract: Objective: Neuropsychiatric symptoms (NPS) are often present in individuals with mild cognitive impairment (MCI) and Alzheimer's disease (AD) dementia. NPS are associated with structural and functional changes in the brain such as atrophy, regional hypometabolism, and hypoperfusion, considered proxies of neurodegeneration. Our objective was to evaluate the association between NPS and regional cerebral tau burden, a more direct representation of neurodegeneration, in cognitively normal (CN), MCI, and AD dementia individuals. Methods: Cross‐sectional NPS were assessed using the Neuropsychiatric Inventory (NPI) in 410 CN, 199 MCI, and 61 AD dementia participants who underwent flortaucipir tau positron emission tomography as part of the AD Neuroimaging Initiative (ADNI). Total NPI score and two factors of NPS (affective and hyperactive) were used in analyses. Linear regression models with backward elimination were employed with NPI as dependent variable and regional tau or tau‐amyloid interaction as predictor of interest. Covariates included education, age, sex, Rey Auditory Verbal Learning Test Total Learning, and Trail Making Test B. Results: There were significant associations ( p  < 0.05) between the NPI variables (total score, Affective factor) and entorhinal and precuneus tau across all participants. These associations were also significant for the tau‐amyloid interaction. These effects were significant in cognitively symptomatic participants (MCI and AD dementia), but not in CN participants. Conclusions: Increased tau burden in the entorhinal and precuneus cortices was modestly associated with greater NPS in MCI and AD dementia. Further evaluation of NPS and their effect on early‐stage AD could aid in finding new interventions and slowing disease progression. Key Points: Neuropsychiatric symptoms (NPS) are common manifestations of early‐stage Alzheimer's disease (AD) In the current study, we found that increased tau burden in the entorhinal and precuneus cortices was modestly associated with greater NPS in MCI and AD dementia These associations were noted with affective symptoms in particular These associations were seen in participants with greater amyloid burden in particular